2019
DOI: 10.26502/jppr.0024
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use Evaluation (DUE) of Ceftriaxone in Mubende Regional Referral Hospital, Uganda: A Cross-Sectional Survey

Abstract: Introduction: Ceftriaxone is a third generation cephalosporin recommended as first line treatment option for a number of diseases in Uganda. However, the National Drug Authority has in the recent past received complaints of suspected treatment failure from clinicians who use different brands of ceftriaxone in Uganda. The main aim of the study was to document the treatment outcome following use of ceftriaxone and evaluating the use of ceftriaxone against the current treatment guidelines in Uganda. Methods: A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Afriyie et al 22 reported that the daily dose of ceftriaxone was administered appropriately to all patients; on the contrary, lowest percentage of patients (18.0%) got appropriate daily dose in Manirakiza et al study. 28 The median prevalence of patients with appropriate daily dose of ceftriaxone was 79.8% (IQR: 40.9–91.0%). Shimels et al 31 reported the highest percentage of patients with appropriate duration of ceftriaxone (91.5%), while the lowest prevalence (18.0%) was reported by Negese et al study.…”
Section: Resultsmentioning
confidence: 96%
“…Afriyie et al 22 reported that the daily dose of ceftriaxone was administered appropriately to all patients; on the contrary, lowest percentage of patients (18.0%) got appropriate daily dose in Manirakiza et al study. 28 The median prevalence of patients with appropriate daily dose of ceftriaxone was 79.8% (IQR: 40.9–91.0%). Shimels et al 31 reported the highest percentage of patients with appropriate duration of ceftriaxone (91.5%), while the lowest prevalence (18.0%) was reported by Negese et al study.…”
Section: Resultsmentioning
confidence: 96%
“…Although ceftriaxone has been recommended as the drug of choice in the management of severe bacterial infections in Uganda's clinical guidelines, 81% of the prescriptions reviewed indicates inappropriate use of ceftriaxone, increasing the risk of bacterial resistance to ceftriaxone and other cephalosporins (5). In addition, the absence of antibiotic therapy guidelines for management of infected chronic wounds promotes indiscriminate use of cephalosporins, increasing the risk of bacterial resistance to cephalosporins as well as complicating the care of infected chronic wounds (6).…”
Section: Introductionmentioning
confidence: 99%